WOMEN AND MEN IN MIDLIFE CRISIS - Dunaeva, Victoria (PEOPLE: International Journal of Social Sciences, 2020)
Uncomfortable period, which men and women experience between the age of 35 and 55, psychologists define as a midlife crisis. At that period some people are getting anxious and loose the nerves over a small issue. They consider it a kind of depression. For them, this period is a true "crisis" and they question every choice they've made during the first half of their life and look back on it with remorse and regret. They are struggling with their mortality, confidence, identity, and accomplishments thus far in life. Negative emotions often evoke them to start radical changes to their current lifestyle. Sometimes they change their life for a better, sometimes they make big mistakes. In my presentation, I would like to take a psychological look at this issue and pay special attention to the differences in experiencing a midlife crisis by women and men. I am also going to define reasons that may lead to this emotional crisis.